Automatic absolute orientation of scanned aerial photographs - Dal Poz, A. P.; Tommaselli, AMG (Institute of Electrical and Electronics Engineers (IEEE), Computer Soc, 1998)
Image orientation is a basic problem in Digital Photogrammetry. While interior and relative orientations were succesfully automated, the same can not be said about absolute orientation. This process can be automated by using an approach based on relational matching and a heuristic that uses the analytical relation between straight features in the object space and its homologous in the image space. A build-in self-diagnosis is also used in this method, that is based on the implementation of data snooping statistic test in the process of spatial resection, using the Iterated Extended Kalman Filtering (IEKF). The aim of this paper is to present the basic principles of the proposed approach and results based on real data.
Keywords: cartography; Digital Photogrammetry; automation; matching; straight feature